The Effect of Trust, Perceived Ease of Use, and Service Features on Trust and Customers’ Interest in Using Mobile Banking - Anggara, Dody Chandra; Nuryakin, Nuryakin; Handayani, Siti Diyah (Ekonomis: Journal of Economics and Business, 2024)
This study aims to describe the effects of security, perceived ease of use, and service features on customers' interest in using mobile banking, with trust as an intervening variable. This study used quantitative approach as the research methodology. Data were garnered using a questionnaire. Participants were 200 customers of BPD DIY bank, recruited using purposive sampling technique. The result showed that service feature affects customers’ trust in using mobile banking, but not their interest. Security and perceived ease of use do not affect customers’ trust and interest. Thus, the bank is recommended to focus on building trust and ensuring the security of its mobile banking service in order to improve customers’ interest in using it. Future studies are recommended to explore other factors affecting customers’ interest in using mobile banking.